Liquid lithium metal processing into ultrathin metal anodes for solid state batteries - Schönherr, Kay; Schumm, Benjamin; Hippauf, Felix; Lissy, Robin; Althues, Holger; Leyens, Christoph; Kaskel, Stefan (Chemical Engineering Journal Advances, 2022)
Lithium metal anodes are among the most promising candidates for further increasing the energy density of lithium ion batteries and all-solid-state batteries. A reduction of the anode thickness by using ultrathin lithium metal films is a crucial requirement to achieve a significant overall reduction of thickness on cell level. However, besides anode stabilization, realizing scalable technologies for an efficient production of thin lithium metal anodes is one of the most challenging obstacles for the success of various next-generation battery chemistries. In this publication we introduce a disruptive lithium melt deposition process for thin lithium metal coating on thin copper current collector foils. The wetting of molten lithium on the substrate can only be achieved through a lithiophilic interlayer. As a result fast and homogeneous lithium spreading on the substrate is enabled allowing roll-to-roll coating with liquid-deposition technologies as demonstrated in this contribution with a speed of several meters per minute and reaching 100 mm width. With this new process the anode thickness can be tuned in a wide range (1–30 µm). Evaluation in a prototype solid battery system shows high electrochemical lithium utilization and no detrimental effects compared to commercially available lithium reference foils.
CRIS-Team Scopus Importer:2022-04-14
Keywords: All-solid-state battery; Lithium deposition; Lithium ion battery; Lithium metal anode